Risk of hospitalization and vaccine effectiveness among COVID-19 patients in the UAE during the Delta and Omicron outbreaks - Albreiki, Mohammed; Mousa, Mira; Azman, Syafiq Kamarul; Vurivi, Hema; Alhalwachi, Zainab; Alshehhi, Fatima; AlShamsi, Safiya; Marzouqi, Nada Al; Alawadi, Tayba; Alrand, Hussain; Oulhaj, Abderrahim; Fikri, Asma; et al. (Frontiers in Immunology, 2023)
A rapid increase in COVID-19 cases due to the Delta and Omicron variants in vaccinated populations has raised concerns about the hospitalization risk and vaccination effectiveness. This case-control study aims to determine the hospitalization risk and vaccine effectiveness of inactivated BBIBP-CorV (Sinopharm) and mRNA BNT162b2 (Pfizer-BioNtech) against the risk of hospital admission between May 28, 2021, to January 13, 2022, during the Delta and Omicron outbreak. The estimation of vaccine effectiveness of 4,618 samples was based on the rate of hospitalization cases at different vaccination statuses adjusted for confounding variables. Hospitalization risk increases in patients affected with Omicron variant if they aged ≤18 years (OR: 6.41 (95% CI: 2.90,14.17); p<0.001), and in patients affected with Delta variant if they aged >45 years (OR: 3.41 (95% CI: 2.21, 5.50); p<0.001). Vaccine effectiveness for fully vaccinated participants against Delta and Omicron variant demonstrated similar effectiveness against hospital admission using the BBIBP-CorV vaccine (94% (95% CI: 90%, 97%); 90% (95% CI: 74%, 96%)) and the BNT162b2 vaccine (95% (95% CI: 61%, 99.3%); 94% (95% CI: 53%, 99%)), respectively. Therefore, BBIBP-CorV and BNT162b2 vaccines utilized in the UAE vaccination program were highly effective against COVID-19-related hospitalization during Delta and Omicron outbreaks, and further effort must be taken to achieve high vaccine coverage rates in children and adolescents in the global context to limit hospitalization risk.